2019
DOI: 10.3390/su11195176
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Alteration at the Upper and Middle Part of the Yangtze River, China: Towards Sustainable Water Resource Management Under Increasing Water Exploitation

Abstract: The human influence on the river ecosystem has increased in recent years to feed the growing demand for water to communities by constructing different water structures. It is essential to understand the potential impacts of water structures on river hydrologic regimes. Thus, this study investigates the influence of the cascade dams located upstream of the Three Gorges Dam on the Yangtze River on the river ecosystem. The study was carried out for the period 2003–2015 for both Cuntan and Miaohe stations. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(29 citation statements)
references
References 52 publications
1
26
0
2
Order By: Relevance
“…moderate alteration). Our results proved that the IHA method encasing RVA targets is an easy and useful tool to quantify the hydrologic alteration in the study area as already reported for many rivers worldwide 36 40 . However, these results were preliminary since only three years of data (2011–2013) were used for IHA calculation for the post-weir period.…”
Section: Resultssupporting
confidence: 85%
“…moderate alteration). Our results proved that the IHA method encasing RVA targets is an easy and useful tool to quantify the hydrologic alteration in the study area as already reported for many rivers worldwide 36 40 . However, these results were preliminary since only three years of data (2011–2013) were used for IHA calculation for the post-weir period.…”
Section: Resultssupporting
confidence: 85%
“…In the context of global warming and frequent human activities, a series of changes have taken place in global and local precipitation patterns, resulting in changes in regional and global water cycles [1][2][3]. The precipitation characteristics (amount, frequency, and intensity) of different grades are expected to change [4].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has altered the seasonal variation in atmospheric circulation-controlled precipitation [38,39]. Climate change has increasingly affected dryness, as well as contributes to the extreme rainfall shortage, more and more, which has become more severe due to anthropogenic pressures [40,41]. For example, North China's droughts in 2009 affected 157 million acres of farmland, and the extreme dryness in Southwest China between 2009 and 2010 reduced bread-basket production to 120 million acres.…”
Section: Introductionmentioning
confidence: 99%